Effects of Crescent Shaped Block Width and Length on Flow Field and Film Cooling Performance - Ahmed, Guelailia; Azzeddine, Khorsi; Ahmed, Slimane Sid; Hamza, Blala; Abdelkader, Slimane (Trends in Sciences, 2023)
Turbine blades and rocket nozzles can be efficiently protected from combustion chamber exhaust hot gases by film cooling technic. A crescent-shaped block placed downstream of the injection hole can significantly improve cooling effectiveness. The main objective of this research work is to investigate the inﬂuence of the crescent-shaped block length and width on film cooling effectiveness. ANSYS CFX was used to conduct analysis of a flat plate configuration with cylindrical holes. Nine configurations of the crescent shaped blocks were considered. For each case, the effect of blowing ratios (0.5 and 1) was investigated. The turbulence model shear stress transport (SST) is used for approximating turbulence. Good agreement was obtained by comparing the analysis results with the experimental data. The result indicated that block width variation has a considerable impact on film cooling performance. However, slight effect of block length on cooling effectiveness was obtained. Comparing all analyzed configurations, the best cooling effectiveness was reached for the model 9 (W = 3d, B = 1.5d). HIGHLIGHTS Rocket nozzles can be efficiently protected from combustion chamber exhaust hot gases by film cooling technic One of the latest techniques to optimize the overall performance of film cooling is adding an obstacle configuration downstream the coolant perforation Film cooling performance is considerably enhanced by placing a crescent shaped block downstream the injection hole The maximum enhancement in overall film cooling effectiveness using the optimal configuration (model 6: W = 2d, B = 1.5d) is about 252 % achieved at a blowing ratio of M = 1 GRAPHICAL ABSTRACT